Chromosomal analysis in Crotophaga ani (Aves, Cuculiformes) reveals extensive genomic reorganization and an unusual Z-autosome robertsonian translocation - Krestschmer, Rafael (Elsevier, 2021)
Abstract: Although cytogenetics studies in cuckoos (Aves, Cuculiformes) have demonstrated an interesting karyotype variation, such as variations in the chromosome morphology and diploid number, their chromosome organization and evolution, and relation with other birds are poorly understood. Hence, we combined conventional and molecular cytogenetic approaches to investigate chromosome homologies between chicken and the smooth-billed ani (Crotophaga ani). Our results demonstrate extensive chromosome reorganization in C. ani, with interchromosomal rearrangements involving macro and microchromosomes. Intrachromosomal rearrangements were observed in some macrochromosomes, including the Z chromosome. The most evolutionary notable finding was a Robertsonian translocation between the microchromosome 17 and the Z chromosome, a rare event in birds. Additionally, the simple short repeats (SSRs) tested here were preferentially accumulated in the microchromosomes and in the Z and W chromosomes, showing no relationship with the constitutive heterochromatin regions, except in the W chromosome. Taken together, our results suggest that the avian sex chromosome is more complex than previously postulated and revealed the role of microchromosomes in the avian sex chromosome evolution, especially cuckoos.